Discriminative and prognostic potential of cerebrospinal fluid phosphoTau/tau ratio and neurofilaments for frontotemporal dementia subtypes - Pijnenburg, Yolande A.L. (Alzheimers Dement (Amst), 2015)
INTRODUCTION: A decreased cerebrospinal fluid (CSF) p-Tau(181) to total tau ratio (p/t-tau) is a biomarker for frontotemporal lobar degeneration with TDP43 inclusions (FTLD-TDP) and for amyotrophic lateral sclerosis (ALS). CSF light chain neurofilaments (NfL) are increased in ALS. We examined whether CSF p/t-tau and NfL are related to ALS status in FTLD-TDP. METHODS: We compared CSF p/t-tau and NfL levels between patients with FTLD-TDP with ALS (n = 15), FTLD-TDP without ALS (n = 17), FTLD-Tau (n = 6), Alzheimer's disease (AD; n = 25), and subjective memory complaints (SMC, n = 24). RESULTS: Apart from FTLD-Tau, all groups differed significantly with increasing p/t-tau ratios from FTLD-TDP with ALS to FTLD-TDP without ALS to AD and SMC. CSF NfL was very high in FTLD-TDP with ALS followed by FTLD-TDP without ALS, AD, and SMC. Both biomarkers correlated with survival. DISCUSSION: CSF p/t-tau ratio and NfL levels are strongly driven by ALS status. These markers, therefore, appear to be more of prognostic than diagnostic significance.